Psychoeducation Using Symbol Modeling Techniques for Enhancing the Subjective Well-Being of Long-Distance Marriage Couples - Kurniady, Dedy; Firman, Firman (Journal of Educational, Health and Community Psychology, 2024)
Long-distance married couples tend to experience anxiety, stress, unhappiness, delayed problem resolution, difficulty finding time together, and feelings of helplessness without their partner. However, previous psycho-educational interventions have not utilized JP-]symbolic modeling techniques and have not specifically focused on long-distance marriages. This study aims to examine the effectiveness of psycho-education using symbolic modeling techniques in enhancing the subjective well-being of long-distance married couples. An experimental matching control study design was used with 16 participants, divided into 8 in the experimental group and 8 in the control group. The subjective well-being scale was used as the instrument for data collection. Data analysis was conducted using the Wilcoxon signed Rank Test and the Mann-Whitney U Test. The results of the study show that psycho-education using symbolic modeling techniques is effective in enhancing the subjective well-being of long-distance married couples. Psycho-educational interventions with symbolic modeling can be used to help long-distance married couples achieve wellbeing, making their marriages more meaningful.